Nanoscale Co/C multilayers for "carbon window" Schwarzchild objective - Bugayev, Ye.A.; Devizenko, A.Yu.; Zubarev, E.N.; Kondratenko, V.V. (Functional Materials, 2007)
The formation features of the Co/C multilayer with ≈2.3 nm period have been studied with aim to form a Schwarzschild objective on a "carbon window" for medical and biological investigations. A sequence of multilayer deposition on curved substrates has been proposed that provides the matched functioning of both objective mirrors. The interaction features of the Co and C layers during deposition, period and reflectivity changes under heating have been considered.